Integrating Media Literacy into School Governance: An Administrative Framework for Digital Citizenship - Andi Muhammad Fadli; Risma Niswaty (ASHA Publishing, 2025)
The rapid escalation of digital disruption has introduced complex challenges to educational environments, ranging from widespread disinformation to ethical dilemmas in digital interactions. While media literacy is frequently addressed through a pedagogical lens, its integration into formal school governance remains underdeveloped. This gap often results in fragmented institutional responses to digital risks, leaving a void in the systematic protection and empowerment of students as digital citizens. This research aims to develop and propose a strategic administrative framework that integrates media literacy into school governance. By shifting the focus from individual classroom practice to institutional policy, the study seeks to establish a sustainable model for fostering robust digital citizenship within educational organizations. The study employed a qualitative research design, utilizing a multi-site case study approach. Data were gathered through in-depth interviews with school administrators, a comprehensive review of institutional policy documents, and focus group discussions involving key educational stakeholders. The analysis focused on identifying administrative barriers and enablers in implementing digital literacy initiatives. The findings indicate that effective media literacy integration requires more than curricular changes; it demands a dedicated administrative commitment through formal policy frameworks, strategic resource allocation, and cross-stakeholder synergy. The research proposes a